The Pay for Success Handbook - Adatto, Suzanne; Brest, Paul (Open textbook library., 2020)
Government agencies frequently contract with nonprofit or for-profit organizations to provide services to improve the well-being of their clients―for example, by reducing recidivism, homelessness, or drug use. Governments have traditionally paid service providers on the basis of the number of clients they treat. The past decade has seen a number of Pay for Success (PFS) or results-based finance (RBF) programs, in which service providers are paid for their outcomes or results. For example, whereas a government agency contracting with a service provider to reduce recidivism among young men released from prison would traditionally have paid the service provider for the hours spent counseling a client, a PFS contract pays the organization for success in reducing the clients’ rate of recidivism from some baseline. This handbook is written for government officials considering the adoption of Pay For Success (PFS) programs and for students in public policy and business schools interested in studying outcomes-oriented government contracts for services. Part One introduces concepts necessary to develop and operate a service delivery program and then surveys some of the issues specific to PFS. Part Two presents two detailed case studies and a number of shorter descriptions of PFS programs. Part Three focuses on the components of PFS programs; it also discusses barriers to their development and ways of overcoming them. An editable file (docx) is also available.